HUBUNGAN PEMANFAATAN LITERASI E-LIBRARY DENGAN MINAT BACA SISWA DI MI MIFTAHUL HUDA WAJAK - Mayla Qonata; Ifa Nurhayati (Universitas Islam Raden Rahmat Malang, 2022)
This research is motivated by the existence of a school library which is very important because the library is the heart of the education that brings the school to life, where the education is carried out. This study aims to determine the relationship between the use of e- library literacy and students' reading interests at MI Miftahul Huda Wajak. The instruments used in this study used observation, questionnaires, documentation and instrument validity. The research method used in this study uses correlational quantitative methods. The results of this study show that the use of e-libraries carried out at MI Miftahul Huda Wajak has a significant relationship with students' interest in reading. This is proven by conducting analytical prerequisite tests, namely the normality test, the Pearson Product Moment correlation test, and the t test statistics for hypothesis testing.